2009
DOI: 10.1007/s00280-009-1110-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of Trk and p75 neurotrophin receptors in tumorigenesis and chemoresistance ex vivo and in vivo

Abstract: The neurotrophin receptors TrkA (NGF receptor) and TrkC (NT-3 receptor) have been shown to be important in staging disease and predicting progression and drug response for various neoplasias such as neuroblastoma, medulloblastoma and prostate cancer. Less is known about the role of the p75 neurotrophin receptor in cancer, but it influences metastatic potential in glioblastoma. To determine the effect of each neurotrophin receptor or coreceptor expression in tumorigenesis, we examined PC12 pheochromocytomas. PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…In our study, high NGF expression was associated with high histologic grade and the presence of distant metastasis, and predicted poorer survival of BRCA patients. The poor prognosis of the patients with NGF-expressing tumor might be related with the ability of NGF-TrkA signaling to induce chemoresistance [31]. Therefore, there is a possibility that NGF-targeted therapy with a combination of conventional chemotherapy could be helpful for BRCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, high NGF expression was associated with high histologic grade and the presence of distant metastasis, and predicted poorer survival of BRCA patients. The poor prognosis of the patients with NGF-expressing tumor might be related with the ability of NGF-TrkA signaling to induce chemoresistance [31]. Therefore, there is a possibility that NGF-targeted therapy with a combination of conventional chemotherapy could be helpful for BRCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that NGF stimulation of undifferentiated embryonic stem cell proliferation is linked to a combined activation of TrkA and p75 NTR , [42] whereas a higher colony-forming potential of phechromocytoma cells has been measured under expression of TrkA or p75 alone. [43] Because the amino terminus is a critical domain for TrkA receptor binding, metal interaction with NGF probably affects the bioactive conformation suitable for receptor activation, as well as discrimination between TrkA and p75, causing, at least in part, the differential effects observed herein. Focusing on the interaction of the metal ion with this region of NGF, which could play a crucial role in receptor discrimination and signalling modulation, becomes of crucial importance; this aspect should also be considered as a function of the ability of NGF to bind to different receptors (even at the same time).…”
Section: A C H T U N G T R E N N U N G [Cul]mentioning
confidence: 94%
“…Elevated levels of NGF in pancreatic cancer cells and high levels of its receptors, TRKA and p75 NTR in the surrounding nerves, have been correlated to poor prognosis and PNI in pancreatic cancer patients [17,18,19,20]. Absence of TRKA in nerve cells results in NGF binding to p75 NTR and leads to activation of pro-apoptotic signals [16,21].…”
Section: Introductionmentioning
confidence: 99%